Removal Efficiency of an Aluminum Based Hydrotalcite-Like-Compound on Arsenic - Dao, Thi Hong Nhung; Vo, Thi Le Ha; Ly, Bich Thuy (Old Journal, 2017)
Hydrotalcite has been considered as a promised adsorbent to remove arsenic. In this study, bench scale studies were conducted to evaluate the effects of adsorbent dose and initial pH on the efficiency for removing arsenic (As) (III) and As(V) by adsorption onto an Al-based hydrotalcite (named MA3). Then the maximum removal adsorption capacity and isothermal models were investigated. The results showed that the optimum pH values for removing As(III) and As(V) were 10 and 5-6, respectively. The investigated MA3 were capable of removing As(III) and As(V) at maximum capacity of 0.14 and 21.9 mg/g, respectively at 25°C and optimum pH. Langmuir isotherm model was better fitted to invested data than Freundlich isotherm model for both As(III) and As(V) with R2 value of 0.93 and 0.99, respectively. It is implied that the adsorption mechanisms were closed with monolayer adsorption.